APPROACHES TO THE TREATMENT OF ACUTE RESPIRATORY INFECTIONS AND INFLUENZA DURING THE SEASONAL INCREASE IN THE INCIDENCE OF DISEASES - L. L. Nisevich; K. S. Volkov; A. A. Alekseeva; A. Yu. Tomilova; V. A. Barannik; K. E. Efendieva (Вопросы современной педиатрии)
Prevention and treatment of acute respiratory infections and influenza in children remain one of the major tasks of practical healthcare. Their importance increases with the beginning of the autumn-winter season. Currently, the problem of choosing effective and safe drugs to treat acute respiratory infections in children is very important. The article discusses the use of various etiotropic and symptomatic drugs to treat acute respiratory infections and influenza in children.